Minimally invasive treatments for benign prostatic hyperplasia: a Cochrane network meta‐analysis. (6th December 2021) - Franco, Juan Victor Ariel; Jung, Jae Hung; Imamura, Mari; Borofsky, Michael; Omar, Muhammad Imran; Escobar Liquitay, Camila Micaela; Young, Shamar; Golzarian, Jafar; Veroniki, Areti Angeliki; Garegnani, Luis; Dahm, Philipp
Abstract : Objective: To assess the comparative effectiveness and ranking of minimally invasive treatments (MITs) for lower urinary tract symptoms (LUTS) in men with benign prostatic hyperplasia (BPH). Materials and Methods: We searched multiple databases up to 24 February 2021. We included randomized controlled trials assessing the following treatments: convective radiofrequency water vapour thermal therapy (WVTT; or Rezūm); prostatic arterial embolization (PAE); prostatic urethral lift (PUL; or Urolift); temporary implantable nitinol device (TIND); and transurethral microwave thermotherapy (TUMT) compared to transurethral resection of the prostate (TURP) or sham surgery. We performed a frequentist network meta‐analysis. Results: We included 27 trials involving 3017 men. The overall certainty of the evidence of most outcomes according to GRADE was low to very low. Compared to TURP, we found that PUL and PAE may result in little to no difference in urological symptoms, while WVTT, TUMT and TIND may result in worse urological symptoms. MITs may result in little to no difference in quality of life, compared to TURP. MITs may result in a large reduction in major adverse events compared to TURP. We were uncertain about the effects of PAE and PUL on retreatment compared to TURP, however, TUMT may result in higher retreatment rates. We were very uncertain of the effects of MITs on erectile function and ejaculatory function. Among MITs, PUL and PAE had the highest likelihood of being the most efficacious for urinary symptoms and quality of life, TUMT for major adverse events, WVTT and TIND for erectile function and PUL for ejaculatory function. Excluding WVTT and TIND, for which there were only studies with short‐term (3‐month) follow‐up, PUL had the highest likelihood of being the most efficacious for retreatment. Conclusions: Minimally invasive treatments may result in similar or worse effects concerning urinary symptoms and quality of life compared to TURP at short‐term follow‐up.